Exchange Rates, Interest Rates and the Global Carry Trade - Martin D. D. Evans; Dagfinn Rime (Norges Bank, 2017)
We empirically examine how the global carry trade affects the dynamics of spot exchange rates and interest rates across 13 countries from 2000, through the world financial crisis, until the end of 2011. Our model identifies the weekly carry trade position in each currency by matching data on forex trading flows with the predictions of a dynamic portfolio allocation problem that exploits the predictability in excess currency returns (deviations from uncovered interest parity). Using these carry positions produce two surprising results: First, in nine countries carry trades are an economically significant driver of interest rate differentials (vs. U.S. rates). Second, the carry trade only affects the dynamics of spot exchange rates insofar as it is contributes to total forex order flow; (i.e., flows generated by the carry trade and all other trading motives). These findings contradict the conventional view that sudden large movements in exchange rates are attributable to the carry trade. They suggest, instead, that the effects of the global carry trade are primarily concentrated in bond markets.
hdl:11250/2495567
Keywords: F3; F4; G1; 330; exchange rate dynamics; microstructure; order flow